Modeling of Small DC Magnetic Field Response in Trilayer Magnetoelectric Laminate Composites - B. Zadov; A. Elmalem; E. Paperno; I. Gluzman; A. Nudelman; D. Levron; A. Grosz; S. Lineykin; E. Liverts (Advances in Condensed Matter Physics)
We consider a magnetoelectric laminate which comprises two magnetostrictive (Ni) layers and an in-between piezoelectric layer (PZT). Using the finite-element method-based software COMSOL, we numerically calculate the induced voltage between the two faces of the PZT piezoelectric layer, by an external homogeneous small-signal magnetic field threading the three-layer Ni/PZT/Ni laminate structure. A bias magnetic field is simulated as being produced by two permanent magnets, as it is done in real experimental setups. For approaching the real materials’ properties, a measured magnetization curve of the Ni plate is used in the computations. The reported results take into account the finite-size effects of the structure, such as the fringing electric field effect and the demagnetization, as well as the effect of the finite conductivity of the Ni layers on the output voltage. The results of the simulations are compared with the experimental data and with a widely known analytical result for the induced magnetoelectric voltage.